Anthropogenic Dispersal of Leishmania (Viannia) braziliensis in the Americas: A Plausible Hypothesis - Marzochi, Mauro Célio de Almeida; Marzochi, Keyla Belizia Feldman; Fagundes, Aline; Schubach, Armando de Oliveira; Miranda, Luciana de Freitas Campos; Pacheco, Raquel da Silva (Frontiers in Tropical Diseases, 2021)
There are several gaps in our knowledge on the origin and spread of Leishmania (Viannia) braziliensis, an etiological agent of cutaneous and mucocutaneous or American tegumentary leishmaniasis, to different biomes, hosts, and vectors, with important epidemiological implications, including the possible existence of an anthroponotic component. Historical, biological, and epidemiological evidence suggests that Leishmania (V.) braziliensis and its variants were preexistent in Amazonia with great genetic variability, where they dispersed with less variability to other regions (clonal expansion). During pre-Columbian times the parasite may have been transported by migrating humans and probably also their dogs, from western Amazonia to the high inter-Andean valleys and from there to other regions of South America. The same thing could have happened later, in the same way, when it spread to non-Amazonian regions of Brazil and other countries of South and Central America, between the late 19th and early 20th centuries, during the so-called Rubber Boom and construction of the Madeira-Mamoré Railway in the Brazilian Amazon, by migrant workers who later returned to their places of origin, transporting the agent. The parasite’s dispersal in genetic correlated clusters, involving unexpectedly distinct ecosystems in Brazil (Amazonian, Cerrado, Caatinga and Atlantic Forest biomes), has continued until the present through human displacement. The infection of certain species of domestic, synanthropic and even wild animals, could be secondary to anthropogenic introduction of L. (V.) braziliensis in new environments. We admit the same phenomena happening in the probable transference of Leishmania infantum (visceral leishmaniasis), and of Yersinia pestis (plague) from the Old world to the New world, generating domestic and wild enzotic cycles from these agents. These assumptions associated with human infections, chronicity and parasite persistence with possibility of recovery of Leishmania in peripheral blood, skin and scars of cured or asymptomatic patients, (that may provide an alternative blood meal), along with the sand flies’ adaptation to the peri-domicile and the high susceptibility of domestic dogs, horses, mules and cats to the parasite, can reinforce the evidence of anthropogenic spread of L. (V.) braziliensis.